(untitled) (Ustozlar uchun, 2026)
In this study, I am going to explore the phraseological units in English and Uzbek through a comparative cultural lens, aiming to uncover the deep-seated values, beliefs, and worldviews embedded in the idiomatic expressions of both languages. Phraseological units—such as idioms, proverbs, and fixed expressions—not only enrich language but also serve as cultural markers that reflect the historical, social, and psychological experiences of a people. By analyzing a selection of commonly used phraseological units from both languages, this research highlights how culture influences linguistic expression and how similar concepts may be verbalized differently depending on cultural context. Particular attention is given to metaphors, symbolic meanings, and cultural connotations found in these expressions. The findings reveal both universal themes and culture-specific elements, offering valuable insights for linguists, translators, and language learners interested in intercultural communication and language teaching. This analysis contributes to the broader field of comparative linguistics and supports the notion that phraseology is a rich source of cultural knowledge.